Quantitative models for the elemental and isotopic fractionations in chondrites: The carbonaceous chondrites - Alexander, Conel M. O'D. (Geochimica et cosmochimica acta, 2019)
A quantitative understanding of the elemental and isotopic fractionations recorded in the compositions of the chondritic meteorites would provide fundamental constraints for astrophysical models of early Solar System evolution. Here it is shown through least squares fitting that almost all features of the bulk elemental and isotopic compositions of the main carbonaceous chondrite (CC) groups, as well as the ungrouped Tagish Lake (C2) meteorite, can be reproduced using mixtures of the same four components. The fractionations amongst the non-CCs (ordinary, Rumuruti and enstatite chondrites) are distinctly different to those in the CCs and are the subject of a separate study (Alexander, 2019). The four CC components are: (1) a ‘chondrule’ (or chondrule precursor) component that partially lost Fe,Ni metal and volatiles, but is otherwise CI-like, (2) the cc-RI component that has a refractory inclusion-like bulk composition and is largely responsible for the refractory element enrichments and nucleosynthetic isotope anomalies in the bulk CCs, (3) anhydrous and reduced but otherwise CI-like matrix that accounts for almost all of the most volatile element (e.g., Zn, Se and C) contents of the CCs, and (4) water with relatively high Δ17O and δ18O values. Comparison of the inferred component compositions to additional meteoritic constraints produces some notable results. The ε48Ca ≈ 8 and ε50Ti ≈ 8 values for the cc-RI component are consistent with the average values for refractory inclusions. On the other hand, the ε54Cr ≈ −10 is not, but is required by the negative correlation between ε50Ti and ε54Cr amongst the bulk CCs. The cc-RI component may be comprised of a more CAI-like sub-component that carries the ε48Ca and ε50Ti anomalies, and a more ferromagnesian sub-component that carries the negative ε54Cr anomalies. The compositions of the volatile and metal subcomponents lost from the ‘chondrule’ component are consistent with condensation models, suggesting that the fractionations predated chondrule formation. The isotopic compositions of chondrules from the more cc-RI-rich CC groups (e.g., CV, CO and CM) seem to require the addition of some of the cc-RI component to their precursors. The assumption that matrix is CI-like is inconsistent with chondrule-matrix complementarity, but is justified by the success of the fits and the relatively uniform and CI-like abundances of organics and presolar grains in the matrices of the most primitive CCs. The inferred Δ17O = 3.5‰ for the water component is consistent with most constraints from secondary phases in the CCs. The large O isotopic mass fractionation (δ18O ≈ 18–21‰) of the water is consistent with ∼89–95% condensation of ice from a vapor under Rayleigh conditions at 150–170 K. The water was entirely accreted with the matrix with fairly constant (0.32 ± 0.06 by wt.) and CI-like (∼0.38 by wt.) water/matrix ratios. These water/matrix ratios are much less than the water/rock ratio of one that is often cited for a nebula of solar composition, but can be explained if much of the C in the CC formation regions was present as CO and CO2, and the abundance of CH4 was low.